Portfolio Choice in a Monetary Open-Economy DSGE Model - Matsumoto, Akito (IMF Working Papers; Working Paper ;, 2005)
This paper develops a two-country monetary DSGE (dynamic stochastic general equilibrium) model in which households choose a portfolio of home and foreign equities, and a forward position in foreign exchange. Some goods prices are set without full information of the state. Home and foreign portfolios are not identical in equilibrium. In response to technology shocks, sticky prices generate a negative correlation between labor income and the profits of domestic firms, biasing portfolios in favor of home equities. In contrast, under flexible prices, labor income and the profits of the domestic firms are positively correlated.